A systematic review of the associations, mediators and moderators of life satisfaction, positive affect and happiness in near-centenarians and centenarians. (3rd April 2022) - Cheng, Adrian; Leung, Yvonne; Brodaty, Henry
Abstract: Objective: Results from studies investigating life satisfaction, positive affect and happiness of near-centenarians (95+) and centenarians are inconsistent. This is the first systematic review to summarise the extant literature on the subjective well-being of this unique age group. Method: Seven electronic databases (PubMed, MEDLINE, EMBASE, PsycINFO, CINAHL, Web of Science and the Cochrane database for systematic reviews) were systematically searched. Subjective well-being was defined as life satisfaction, positive affect and happiness. A narrative synthesis of relevant articles was undertaken. Results: Of 28 studies eligible for inclusion in this review, 20 predominantly examined life satisfaction, 11 positive affect and 4 happiness. Sex and other demographic variables were not significant predictors of subjective well-being. In contrast, greater perceived health was significantly associated with higher levels of life satisfaction and positive affect. Fatigue and visual impairment were significantly correlated with lower levels of life satisfaction and positive affect. However, there was considerable heterogeneity in the findings on physical, cognitive and social associations, mediators and moderators. Conclusion: The large discrepancy of results in the literature may be explained by methodological differences between studies. Centenarian research needs a clearer definition of life satisfaction, positive affect and happiness as their operationalisation is inconsistent. An international consortium of centenarian studies could facilitate cross-cultural comparisons on subjective well-being. Future research should be directed towards interventions that promote subjective well-being in the oldest-old.